Protein Carbonyl Measurement by Enzyme Linked Immunosorbent Assay - (:unkn) unknown (John Wiley and Sons, 2011)
[No abstract available]
Keywords: Cells, ameliorating modifications; Detection in aquatic systems; Methods, measuring protein carbonyls; Protein carbonyl formation; Protein carbonyl measurement and elisa; Protein carbonyl measurement by elisa; Reagents for carbonyl elisa method; ROS, modifications in proteins and dna; Two-dimensional electrophoresis and immunoblotting